PRINSIP CAVEAT VENDITOR DAN CAVEAT EMPTOR DALAM SENGKETA KETIDAKSESUAIAN BARANG DALAM KONTRAK JUAL BELI INTERNASIONAL - Dini Kartika Salsabila (BELLI AC PACIS (Jurnal Hukum Internasional), 2021)
In national and international trade it is common to encounter trade disputes, one of the disputes is the non-conformity of the traded goods. This can occur due to various factors originating from both the seller and the buyer. Hence, trade contracts must be made explicitly regarding the rights and obligations of the parties as well as clear arrangements for liability of parties that can facilitate the parties in the event of a dispute in the future and brought into the realm of international arbitration then it can be resolved by the guidance of Article 35 of the CISG. This article will be discussed in detail about the provisions of the conformity specifications of goods that are regulated internationally in Article 35 of the CISG and pay attention to the principle of caveat venditor and caveat emptor as supporting rules for Article 35 of the CISG.